Literature Review on Auditor Independence - Masyitah, Emi (Ridwan Institute, 2023)
This study aims to provide an overview of the development of auditor independence research. Data were taken from articles published in Scopus indexed international journals from American Accounting Association publishers, Emerald, Wiley, Elsevier, Routledge, Academic Press Inc, and Taylor and Francis Ltd. Samples were taken from 2002 to 2022 as many as 27 auditor independence articles. The method of analysis is through classifying articles based on the research method used, the name of the journal, the year of publication, and the country of origin of the first author. In general, the results of the study found that research on auditor independence has increased from year to year and is still an interesting research topic to study.